Paternal genetic diversity, differentiation and phylogeny of three white yak breeds/populations in China - Jing Luo; Xudong Wei; Wenxian Liu; Shengmei Chen; Zulfiqar Ahmed; Wenping Sun; Chuzhao Lei; Zhijie Ma (Scientific Reports, 2022)
Abstract The white yak, a type of unique and valuable farm animals on the Qinghai-Tibet Plateau, are mainly distributed in Tianzhu (County of Gansu Province), Menyuan, Huzhu and Ledu (three Counties of Qinghai Province) in China. In the present study, the Y-chromosomal genetic diversity, differentiation and phylogeny of three Chinese white yak breeds/populations (Tianzhu, Huzhu and Menyuan) were comprehensively explored using five Y-SNPs (SRY4, USP9Y, UTY19, AMELY3 and OFD1Y10) and one Y-STR (INRA189) markers. The results showed that six Y-haplotypes (H1Y1, H9Y1, H10Y1, H11Y2, H12Y2 and H13Y2) were identified in 97 male yak from three white yak breeds/populations. Among these haplotypes, H1Y1, H10Y1 and H11Y2 were shared by all of breeds/populations and H12Y2 was shared by Tianzhu and Huzhu populations. However, H9Y1 and H13Y2 haplotypes were only detected in Menyuan and Tianzhu white yak populations, respectively. The Y-haplotype diversity was maximum in Huzhu white yak (0.7500 ± 0.0349), the medium in Tianzhu white yak (0.6881 ± 0.0614) and the lowest in Menyuan white yak (0.5720 ± 0.0657). The total Y-haplotype diversity of three white yak breeds/populations was 0.7567 ± 0.0233, indicating rich paternal genetic diversity in white yak. The F ST values showed a moderate differentiation between Tianzhu and Menyuan (F ST  = 0.0763, P < 0.05) populations, but a weak differentiation between Huzhu and Tianzhu white yak breeds/populations (F ST  = 0.0186, P > 0.05) and Huzhu and Menyuan (F ST  = − 0.005, P > 0.05) populations. The clustering analysis revealed a close genetic relationship between Huzhu and Menyuan white yak, both were far from Tianzhu white yak breed. The phylogenetic analyses showed that white yak had two Y-haplogroups/lineages (Y1 and Y2) with two potential paternal origins. The findings of present study provide new insight into the basic information for the formulation of molecular breeding programs of white yak. Moreover, it also contributes to the conservation and utilization of this special animal genetic resource.